Comparison of Nutrition and Health Improvement Policies Between the Indonesian and Thailand Governments - Abid Ghossan Albaihaqi; Arif Zainudin; Agus Setio Widodo (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2026)
Nutritional problems remain a major challenge in Southeast Asia, characterized by the high prevalence of stunting, micronutrient deficiencies, and the increasing incidence of overnutrition, all of which affect public health quality and productivity. Differences in outcomes between Indonesia and Thailand indicate variations in the effectiveness of nutrition policies that warrant further examination. This study aims to compare the policies and strategies of Indonesia’s National Nutrition Agency and Thailand’s Bureau of Nutrition in improving nutritional status and public health. The research employs a descriptive qualitative method with a comparative approach through a systematic literature review, using secondary data from 111 selected scientific articles out of 1,206 relevant publications, analyzed through thematic analysis with the assistance of RStudio software. The findings reveal that Indonesia tends to adopt a top-down approach through large-scale national programs but still faces challenges in cross-sectoral coordination and disparities in regional implementation. In contrast, Thailand emphasizes a community-based approach that is integrated, participatory, and adaptive to socio-cultural contexts, making it more effective in reducing malnutrition rates. The study also highlights that policy effectiveness is influenced by institutional factors, cross-sector collaboration, and community participation.